Sugars and organic acids in clones and cultivars of arctic bramble and hybrid. Sensory evaluation of juices and jellies - Häkkinen, Sari; Kokko, Harri; Kärenlampi, Sirpa; Paasisalo, Sirpa (Agricultural and Food Science, 1995)
Arctic bramble (Rubus arcticus L.) and its hybrid (Rubus arcticus L. nothosubsp. stellarcticus G. Larsson) are both cultivated in Finland. Sugars and major organic acids were analysed in several arctic bramble clones and cultivars (n = 19) and arctic bramble hybrids (n = 5) by gas chromatography. The main sugar in the berries was sucrose, and the main organic acid was citric acid. The average total contents of sugars in the berries of arctic brambles and arctic bramble hybrids were 5.0 g (CV = 0.1) and 4.7 g (CV = 0.2) per 100 g of fresh weight, respectively. The average total contents of organic acids in the berries of arctic brambles and arctic bramble hybrids were 0.6 g (CV = 0.3) and 1.5 g (CV = 0.5) per 100 g of fresh weight, respectively. Changes in these compounds during the harvesting period were also studied in mixed samples. Moreover, the sensory properties of juices and jellies prepared from several arctic bramble clones were evaluated by quantitative sensory profiling. The sugar/acid ratio obtained from the chemical analyses of the berries was compared with the sensed sweetness and sourness of juices and jellies. Suomessa viljellään mesimarjaa (Rubus arcticus L.) ja jalomaarainta (Rubus arcticus L. nothosubsp. stellarcticus G. Larsson), ja erityisesti mesimarja on haluttu raaka-aine elintarvike- ja viiniteollisuudessa. Tämän tutkimuksen tavoitteena oli analysoida kaasukromatografisesti tärkeimmät sokerit ja orgaaniset hapot 19 mesimarjalajikkeesta tai -kannasta ja 5 jalomaarainlajikkeesta. Marjojen tärkein sokeri oli sakkaroosi, ja tärkein orgaaninen happo sitruunahappo. Marjojen sokeri- ja orgaanisten happojen pitoisuudet vaihtelivat eri lajikkeilla ja kannoilla. Keskimääräinen mesimarjojen sokeripitoisuus oli 5,0 g (vaihteluväli 3,8-6,1 g) ja jalomaarainlajikkeiden 4,7 g (vaihteluväli 3,4-5,7 g) 100 g:ssa tuoreita marjoja. Keskimääräinen happopitoisuus oli mesimarjoissa 0,6 g ja jalomaaraimissa 1,5 g 100 g:ssa tuoreita marjoja. Sokereiden ja orgaanisten happojen muutoksia tutkittiin satokauden ...